Mental Accounting in Grocery Settings: Evidence of In-Store Slack from the Expected Cost of the Basket - Mauricio Valle; Rodrigo Morrás (Journal of Technology Management & Innovation, 2023)
The evidence from field studies in retail environments suggests in-store slack is part of the consumer’s purchasing budget. These funds are used as a self-control mechanism so as not to exceed the budget. We propose a conceptualization of in-store slack as the difference between the expected cost of the basket and the total budget allocated for the present visit to the store. Then, we explain this slack from the composition of the customer’s basket in three branches of a supermarket chain. Using data taken from a field study, we found evidence that in-store slack is used fundamentally for unplanned purchases, which is consistent with the notion that these funds are used to finance products where the decision to purchase is made in-store. We also found evidence of unused budgetary resources being transferred to in-store slack to finance unplanned products. This supports the idea that consumers are flexible when managing their mental accounts.